Cephaeline and emetine production and antimicrobial activity of the Ipecac root via optimized maturity-based harvesting and processing - Rodríguez-Víquez, Marco Antonio (2025)
[Objective] This study aimed to determine whether there is an optimal harvest time for cephaeline, emetine, and total alkaloids in Ipecac (Carapichea ipecacuanha [Brot.] L. Andersson) production. In addition, the relationship between antibiotic activity and harvest time was tested. Ipeca is an herb with medicinal properties that is grown in northern Costa Rica. The root of this plant is valued based on its alkaloid concentration, which underlies its numerous biological activities. [Methodology] Two Ipecac fields from northern Costa Rican producers were sampled every ~2 months for one year. Samples were dried (via sun and oven), ground, extracted, and analyzed using HPLC and titration to evaluate the alkaloid concentration. Antimicrobial activity was also determined using the Kirby-Bauer test. [Results] Main findings revealed that there is no significant difference between oven-dried and sun-dried samples. In addition, there is an increase in total alkaloid production in roots during the first 16 months, as well as a variation in alkaloid composition: the cephaeline/emetine ratio increases after 16 months. [Conclusions] The highest alkaloid concentration occurs when plants are harvested between 16 and 19 months old. Additionally, the antibiotic activity reaches its maximum at 16 months, and the cephaeline/emetine ratio is two at the same harvest time.